Semantic Structure of Javanese Verb ‘to cut’: Natural Semantics Metalanguage Analysis - Rizal D Syifa; Agus Subiyanto (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2022)
The verb ‘to cut’ in Javanese is an interesting verb to study. This is because the tools, the objects, the way it is use, and the results will affect the selection of the lexicon used. This qualitative descriptive study focuses on describing the semantic structure of the verb ‘to cut’ in Javanese using the Natural Semantic Metalanguage (NSM) approach which was initiated by Wierzbicka (1996) using one of the theoretical concepts of NSM. The source of the data was obtained from the intuition of the researcher as a native speaker of the Javanese language assisted by using the Bausastra Jawa dictionary and Kamus Bahasa Jawa - Bahasa Indonesia I. The data analysis technique used four steps including determining the original meaning, deriving meaning, determining polysemy, and paraphrasing meaning. The results of the research show that there are 12 lexicons ‘to cut’ in Javanese which have close meanings, i.e., nyukur, nyunati, mbeleh, nguliti, nugel, nggraji, negor, mbabat, ngrajang, nyacah, nyuwek and nggunting, which are then grouped into 6 categories based on the object.